Aspectos agronômicos e bromatológicos de leguminosas forrageiras na Zona da Mata Seca de Pernambuco - TEIXEIRA, Vicente Imbroisi (2008)
The aim of this work was to evaluate the agronomic and bromatologic aspects of nine herbaceous forage legumes. Legumes studied included Clitoria ternatea L., Desmodium heterocarpon (L.) DC. Subsp. Ovalifolium (Prain) Ohashi cv. Itabela, Arachis pintoi Krap & Greg. cv. Amarillo, Pueraria phaseoloides (Roxb.) Benth, Stylosanthes guianensis (Aubl.) Sw. cv. Bandeirante, cv. Cook and cv. Mineirão and Stylosanthes macrocephala MB Ferreira & NM Sousa Costa cv. Pioneiro. The following response variables were measured: soil cover, occurrence of pests and diseases, plant height, fresh matter production, stand, seed production, regrowth vigor, tiller number, NDF, ADF, lignin, crude protein, and ether extract concentrations of leaves and stems. Four cuts were performed during the experimental period. Cutting intensities were at the ground level for the first cut and 5 cm for the following cuts. Itwas used a complete randomized block design with three replications per treatment. Clitoria ternatea showed the greatest fresh matter yield summed along the four cuts (45,6t/ha/432 d) and the legume showed one of the greatest CP concentrations, both for leaves (35,4%) and for stems (15,8%). At 43 days after transplanting, C. mucunoides showed the greates soil coverage. During the 432 days of experimental period, the S. guianensis cultivars did not flower, however, C. mucunoides, C. ternatea, and Pioneiro presented the greatest seed production. Arachis pintoi, C. ternatea and C. mucunoides showed greater potential for forage production in this region, and C. ternatea presented the most promising results in terms of chemical composition.